1988
DOI: 10.1073/pnas.85.9.3095
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule 1 (ICAM-1) has a central role in cell-cell contact-mediated immune mechanisms.

Abstract: The role of Intercellular adhesion molecule 1 (ICAM-1) in immune function was probed by using the Wehi-CAM-1 (W-CAM-1) monoclonal antibody. This antibody blocks aggregation of cell lines mediated by the ICAM-1 molecule and is here shown to block homotypic binding of purified populations of activated T and B lymphocytes (blasts) and also aggregation of mixed T-and B-cell blasts. We also demonstrate that W-CAM-1 inhibited T-cell adhesion to normal human endothelial cells, the first step in lymphocyte egress into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
157
1
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(167 citation statements)
references
References 24 publications
8
157
1
1
Order By: Relevance
“…De novo expression of ICAM-1 has been described on different cell types in inflammatory lesion during rejection, and on melanoma cells [41]. Experimental studies have also shown that antibodies against ICAM-1 inhibit leukocyte adhesion to endothelial cells, granulocyte migration through endothelium, and mixed lymphocyte reactions in vitro [42]. In addition, in vivo administration of antibodies raised against ICAM-1 reduced neutrophil infiltration into the inflamed lungs in the rabbit and protects the development of SAO-induced injury.…”
Section: Discussionmentioning
confidence: 99%
“…De novo expression of ICAM-1 has been described on different cell types in inflammatory lesion during rejection, and on melanoma cells [41]. Experimental studies have also shown that antibodies against ICAM-1 inhibit leukocyte adhesion to endothelial cells, granulocyte migration through endothelium, and mixed lymphocyte reactions in vitro [42]. In addition, in vivo administration of antibodies raised against ICAM-1 reduced neutrophil infiltration into the inflamed lungs in the rabbit and protects the development of SAO-induced injury.…”
Section: Discussionmentioning
confidence: 99%
“…13 CD54 is an important ligand for leukocytes and is believed to be involved in immune surveillance. 15,16 Intravenous administration of MAb against human CD54 (UV3) results in long-term survival in SCID mice injected with human myeloma cells. 17 Moreover, UV3 was also highly effective in treating mice with advanced tumors.…”
mentioning
confidence: 99%
“…Two adhesion events that are of particular interest are the interaction between ICAM-I (CD54) and C D l l d C D 1 8 complex, and between CD2 and leukocyte function-associated antigen 3 (LFA-3) (CD58), not only because of their demonstrated role in cell-to-cell adhesion (17)(18)(19), but also because of their ability to facilitate antigen presentation to T lymphocytes and cytolysis (20)(21)(22)(23). Therefore, w e used a quantitative in vitro cellular adhesion system t o examine the relative contributions of ICAM-1-CD1 ldCD18 and of CD2-LFA-3 to T lymphocyte adhesion to cytokine-activated human synovial fibroblasts.…”
Section: T Lymphocyte Adhesion To Human Synovial Fibroblastsmentioning
confidence: 99%